Trading Volume, Trading Price, Trading frequency and Stock Return Volatility of Everest Bank Limited - Bashu Neupane,; Dipendra Neupane,; Puskar Baral, (Pravaha, 2022)
The primary objective of this study is to measure the relationship between stock returns, trading volume, trading frequency and trading price volatility of Everest Bank Limited. We analyzed studies using descriptive studies and randomized comparative studies. A 12-year panel data set was used. 1873 observations are analyzed to draw correct conclusions about the study. Descriptive models provide data on average stock returns, trading volume, and price volatility. EBL investors have faced high risk when investing in stocks for 12 years. There is an important and positive relationship between them. Likewise, volume and price have a positive and significant impact on stock returns.